Pro-Poor Tourism: Unlocking the Opportunities for the Pooro Kuakata Sea-Beach of Bangladesh - Farzana, Fawzia (Journal of Bangladesh Institute of Planners, 2014)
Pro-Poor Tourism (PPT) is an innovative idea in tourism sector that has been introduced to strengthen economic well being of local communities. It emphasizes participation of poor people of the society, makes them engaged in employment and self-help sector and establishes a synthesis between development of tourism by upgrading the degree of livelihood status of poor people so that poverty eradication is possible and socio economic status of poor people is improved. However, a number of barriers prevent the poor from participating in such programs that need to be addressed before the benefits of PPT can be realized. Here, the ultimate objective is to achieve the net benefits that go in favor of poor people. Tourism has changed to some extent the socio-economic status of the poor of surrounding villages of Kuakata Sea Beach. However, the villagers also find it difficult to be actively engaged in tourism due to some constraints. These barriers need to be eliminated to get the benefit of tourism in respect of poverty reduction. The purposes of this study are to investigate the potentiality, constraints and actions to overcome those constraints of pro-poor tourism in Kuakata, Bangladesh. Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 97-109